2017
DOI: 10.1097/md.0000000000007861
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ADD1 Gly460Trp gene polymorphism and essential hypertension in Madeira Island

Abstract: Essential hypertension (EH) is a complex disease in which physiological, environmental, and genetic factors are involved in its genesis. The genetic variant of the alpha-adducin gene (ADD1) has been described as a risk factor for EH, but with controversial results.The objective of this study was to evaluate the association of ADD1 (Gly460Trp) gene polymorphism with the EH risk in a population from Madeira Island.A case-control study with 1614 individuals of Caucasian origin was performed, including 817 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The authors concluded that ADD1 Gly460Trp-polymorphism is an independent genetic marker for AH occurrence in the Japanese population [ 12 ]. An association between T allele and AH development was revealed among Russians [ 15 ], Chinese [ 14 ], Japanese [ 11 ], inhabitants of Madeira [ 18 ], Tunisia [ 16 ], North Africa [ 13 ], and Asian population [ 17 ]. The results we have obtained also indicate an association between ADD1 Gly460Trp-polymorphism and AH occurrence in Ukrainians and demonstrate the higher T allele frequency in patients with salt-sensitive AH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that ADD1 Gly460Trp-polymorphism is an independent genetic marker for AH occurrence in the Japanese population [ 12 ]. An association between T allele and AH development was revealed among Russians [ 15 ], Chinese [ 14 ], Japanese [ 11 ], inhabitants of Madeira [ 18 ], Tunisia [ 16 ], North Africa [ 13 ], and Asian population [ 17 ]. The results we have obtained also indicate an association between ADD1 Gly460Trp-polymorphism and AH occurrence in Ukrainians and demonstrate the higher T allele frequency in patients with salt-sensitive AH.…”
Section: Discussionmentioning
confidence: 99%
“…A number of population studies revealed an association between the Gly460Trp T allele ( ADD1 gene) and AH development [ 10 18 ]; however, in others, this link is absent [ 19 22 ]. It should be noted that data on the association between ADD1 Gly460Trp-polymorphism and the AH occurrence remain controversial and demonstrate the interpopulation differences in the association of gene polymorphic variants with the risk of AH development.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation in several genes may account for the increased salt sensitivity of certain individuals ( 12 ). Moreover, when regarding the predisposition towards GC, individuals who are not sensitive to salt may ingest larger amounts of salt than necessary or normal when attempting to taste salt in food, thus increasing the likelihood of developing GC.…”
Section: Introductionmentioning
confidence: 99%